CTENOCHAETUSMARGINATUS (VALENCIENNES) (PISCES: ACANTHURIDAE) EN LA ISLA DE GORGONA: PRIMER REGISTRO DEL GENERO PARA EL PACIFICO COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
The genus Ctenochaetus is reported in the waters of the Colombian Pacific based on two specimens of C. marginatus (Valenciennes) collected in 1993 at Gorgona Island (2°59, N, 78° 12, W). These specimens differ in several morphometric characteristics from those previously examined. Such differences appear to be an artifact of the small number of specimens formerly examined and the consequent narrow ranges reported. We suggest that temperature variability affects the distribution of C. marginatus in the tropical eastern Pacific.